Relationship between fiscal instruments and investments of industrial SMEs and LEs in Poland - Woźniak, Maciej; Lisowski, Robert (Managerial Economics, 2017)
The authors used statistical tools to analyze the relationship of fiscal support instruments and the level of the investment of industrial micro, small, and medium–sized enterprises in comparison to large companies in Poland in the years 2006–2014. The results revealed that there is a significant relationship between the level of investment in micro–, small–, and medium–sized enterprises and the majority of tax instruments. There is a negative relationship between the instruments and some of other factors that should influence on the investments of enterprises.